Health diagnosis of the Cañales de Bijahual community, Portoviejo, period June - September 2023 - Andrade, Nelson E.; Espejero, Joseph G.; Monroy, Emily S.; Párraga, Daver S.; Ávila, Zulema; Espinel, Patricia M. (Revista Gregoriana de Ciencias de la Salud, 2025)
This study examines the health situation of the Cañales de Bijahual community, Abdón Calderón, Portoviejo canton, during the period June-September 2023. It is a cross-sectional, descriptive, and observational research with a mixed quantitative-qualitative approach. Data collection included demographic characterization, living conditions, and the main health problems of the community. The results revealed a heterogeneous population structure by age and sex, with identified dispensary groups associated with communicable diseases such as dengue and non-communicable chronic diseases like hypertension and type II diabetes mellitus. Additionally, the primary barriers to accessing health services were found to be related to the community's geographic location, which contributes to the persistence of these health issues. In conclusion, it is essential to implement intervention strategies that promote access to health services and educational programs focused on preventing and managing these diseases, aiming to improve the population's quality of life and prevent long-term complications.